Evaluasi Program INPOWER-CARE dalam Perspektif Triple Bottom Line pada Kelompok Tani Hutan Gunung Kamojang - Diona Marva Leilani; Dito Hastha Krisandy (LPkM Universitas Bakrie, 2026)
This program aims to evaluate the implementation of the Triple Bottom Line (TBL) principle in the INPOWER-CARE program which is a form of CSR of PT PLN Indonesia Power UBP Kamojang, especially in the context of coffee cultivation by the Kelompok Tani Hutan (KTH) Gunung Kamojang. This is due to the fact that there has been no evaluative study on the real impact of the group's coffee cultivation program seen from the TBL principle. The approach used in this research is qualitative with the type of case study, through in-depth interviews, participatory observation, and literature study. The results showed that the INPOWER-CARE program in coffee cultivation of KTH Gunung Kamojang succeeded in improving the social welfare of the community, creating new economic opportunities, and supporting environmental sustainability through forest conservation. However, challenges remain in terms of business sustainability management, market access, and the effectiveness of program implementation in the long term. Based on these findings, this study suggests strengthening the strategic planning aspect to ensure a more sustainable impact as well as increasing the capacity of the community to be more self-reliant after the CSR period has ended.